Community Empowerment for Stunting Prevention: A Quasi-Experimental Study in Indonesia - Agung Suharto; Budi Joko Santosa; Suparji Suparji (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Stunting remains a major public health challenge in Indonesia, with long-term consequences for human resource quality. Empowering Posyandu (integrated health post) cadres through theory-based approaches is considered a strategic intervention to strengthen prevention efforts.Objective:This study aimed to evaluate the effectiveness of a community empowerment model grounded in the Health Belief Model (HBM) and the Theory of Planned Behavior (TPB) in improving preventive behaviors among Posyandu cadres. Methods: A quasi-experimental design with a non-equivalent control group and pretest–posttest approach was employed. The study was conducted in Magetan Regency, East Java Province, from January to September 2023. The intervention group was drawn from Panekan Sub-district and the control group from Plaosan Sub-district, with geographic separation used to minimize contamination. The study population comprised 400 cadres, from which 200 respondents were recruited proportionally and selected using random sampling within each sub-district (intervention = 100; control = 100). The intervention consisted of structured training modules integrating HBM and TPB constructs, including risk perception, benefits of prevention, self-efficacy, barrier reduction, and behavioral planning. Data were collected using a validated Likert-scale questionnaire measuring perceived susceptibility, perceived benefits, attitudes, intentions, subjective norms, and preventive behaviors. Analyses employed paired-samples t-tests for within-group comparisons and independent-samples t-tests for between-group differences, with significance set at p < 0.05. Results: The intervention group demonstrated statistically significant improvements across all measured variables (p < 0.001). Preventive behavior scores increased from 12.11 (SD = 1.06) at baseline to 21.10 (SD = 1.87) post-intervention. Between-group analyses confirmed higher posttest scores in the intervention group compared to controls (p < 0.001). Conclusion: Empowerment training based on HBM and TPB was effective in enhancing cadres’ cognitive and behavioral components related to stunting prevention. These findings provide preliminary evidence supporting the integration of theory-driven empowerment models into community health programs, while highlighting the need for sustained training and longer-term evaluation to ensure durability of behavioral change.